1995
DOI: 10.1093/infdis/172.2.490
|View full text |Cite
|
Sign up to set email alerts
|

Deferoxamine B but Not Deferoxamine G1 Inhibits Cytokine Production in Murine Bone Marrow Macrophages

Abstract: The iron chelator deferoxamine (DFO) B enhances virulence of Yersinia enterocolitica and modulates cellular immune responses. Since cytokines mediate effector mechanisms in resolution of yersiniae from infected tissues, the impact of DFO B and DFO G1 on cytokine production by murine bone marrow macrophages (BMM) was investigated. BMM were stimulated with lipopolysaccharide (LPS) of Salmonella typhimurium or infected with Y. enterocolitica. DFO B inhibited interleukin (IL)-6, IL-12, and tumor necrosis factor (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
13
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…DFO inhibits proliferation of T and B lymphocytes and cytokine production of macrophages and modulates interaction of polymorphonuclear leukocytes with yersiniae (3,21). In keeping with these observations, we and others have demonstrated that DFO increases pathogenicity of Y. enterocolitica in mice, resulting in fatal septicemia and shock (5,39,40).…”
supporting
confidence: 82%
See 1 more Smart Citation
“…DFO inhibits proliferation of T and B lymphocytes and cytokine production of macrophages and modulates interaction of polymorphonuclear leukocytes with yersiniae (3,21). In keeping with these observations, we and others have demonstrated that DFO increases pathogenicity of Y. enterocolitica in mice, resulting in fatal septicemia and shock (5,39,40).…”
supporting
confidence: 82%
“…In an attempt to find drugs with comparable iron binding capacity but reduced Yersinia virulence-enhancing properties, DFO B has been compared with DFO G in terms of its biological properties for bacteria and host cells (3,5). DFO G was found to have fewer immunosuppressive properties and to exert less enhancement of virulence of Yersinia in vivo (5).…”
mentioning
confidence: 99%
“…Furthermore, P. aeruginosa pyochelin is implicated, by virtue of being a catalyst for generating a hydroxyl radical, as a mediator of tissue damage (15). Finally, several different siderophores are capable of directly altering, at least in vitro, the viability and function of cells of the immune system, including T cells and macrophages (2,3,20,47,54,95). Thus, future examination of the role of legiobactin in infection needs to consider the variety of ways that siderophores can act.…”
Section: Discussionmentioning
confidence: 99%
“…The study of virulence in the mouse infection model with a naturally high-pathogenicity-island-negative Y. enterocolitica of serotype O:9 and O:3 is further complicated by the fact that mice have to be pretreated with desferrioxamine B (DFO) to achieve mouse virulence, and this pretreatment may influence pathogenicity because of the immunosuppressive effect of DFO (4). The virulence of yopQ and yopM (43) mutants in the mouse model was previously studied by using Y. enterocolitica O:9.…”
Section: Discussionmentioning
confidence: 99%